ANALISIS KINERJA U-TURN DI DEPAN SUPERINDO SUKARAMI JALAN KOLONEL HAJI BURLIAN - Ayuningtia, Noventa Wijaya; Rosyad, Farlin; Prawira, Wanda Yudha; Amin, Muhammad (Ensiklopedia of Journal, 2025)
The high volume of vehicles on Jalan Kolonel Haji Burlian in Palembang causes congestion, particularly at conflict points facilitated by median openings. The presence of Superindo Sukarami, located at the median opening at KM 9 of Jalan Kolonel Haji Burlian, has created a new congestion problem on this road segment. This issue arises due to many Superindo Sukarami visitors parking their vehicles on the roadway, as well as visitors exiting the parking area and making an immediate U-turn. This study aims to analyze traffic volume, road capacity, level of service (LOS), and provide solutions to improve U-turn performance. The research was conducted through field surveys to collect primary data from both road directions, as well as secondary data collection, which were then analyzed based on the Indonesian Road Capacity Manual (PKJI, 2023). The analysis results show that the highest traffic volume from the Fly Over Bandara – JM Sukarami direction was 1,943.3 pcu/hour, and from the JM Sukarami – Fly Over Bandara direction was 2,214.4 pcu/hour. The calculated road capacity was 2,924 pcu/hour, resulting in a degree of saturation of 0.66 (LOS C) from Fly Over Bandara – JM Sukarami and 0.76 (LOS D) from JM Sukarami – Fly Over Bandara. By implementing proper parking arrangements and traffic management, the road segment’s performance is expected to improve. Keywords : U-Turn, Traffic Performance, Capacity, Level of Servive (LOS)